Prevalence of Diarrhea and Association with Socio-Demographic Factors among Children Under Five in Mayo Camp-Khartoum State Sudan - Elmanssury, Ahmed, Elnadif, Dafalla, Safa, Abdalla (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diarrhoeal diseases remain among the most common causes of mortality and morbidity in children, particularly in low- and middle-income countries (LMICs). In 2013, of the 6.3 million children worldwide who died before they reached their fifth birthday, about half (3.2 million) died from infectious diseases, with diarrhoea killing more than 500,000 children. Sudan has one of highest prevalence rates of diarrhoea and Global Acute Malnutrition. Objectives: To determine the prevalence of diarrhea and impact of socio-demographic factors on the prevalence among Children under five years, Methodology: a community-based cross-sectional research was carried out to study the prevalence of diarrhoea among children under 5 years of age. Results: The average prevalence of diarrheal cases occurring during the 2 weeks preceding the interview was 35.0 percent (n = 311). The prevalence was higher among boys than among girls (25% and 10%, respectively). Our research showed that sociodemographic factors such as family size, number of < 5 siblings and occupation of the mother were not significantly correlated with diarrheal disease in children under 5 years of age, whereas the research showed a high significance between the educational level of the mother and the diarrheal disease family income in children under 5 years of age. Conclusions: our study showed High prevalence of diarrhea in children under the age of five, with the highest prevalence among male compared with female. correlation highly associated between education of mothers, income levels, and diarrheal disease.